Analisis Profil Fisika Kimia dan Farmakokinetik Senyawa Pentagamavunon-1 Secara Komputasi - Eva Kholifah; Endah (Duta Pharma Journal, 2022)
Pentagamavunon-1 (PGV-1) is a curcumin analog which is known to inhibit the growth of cancer cells, bacteria and inhibit free radicals as an antioxidant agent. The purpose of this study was analyzed the pharmacokinetic profile and physicochemical properties of PGV-1 computationally. The predicted parameters were Lipinski rule of five, bioavailability, Blood Brain Barrier (BBB) ​​absorption, GI absorption, P-gp substrate, and prediction of metabolic enzymes involved in drug ADME processes. The results of this study indicate that the compound PGV-1 complies with the Lipinski rule of five with the characteristics of a molecular weight of 348.43 g/mol, hydrogen donor 2, hydrogen acceptor 3, Log P 4.71 and molar refractory 40-130. PGV-1 could absorb through the GI and can pass the blood brain barrier passively without P-gp protein. Several enzymes involved in the metabolism of PGV-1 are CYP2C19, CYP2C9, CYP 3A4. Thus, our finding suggest that PGV-1 can be developed as a drug target compound for active oral drugs.